Socio-Demographic Factors Associated with the Risk of HPV Infection Among Sexually Active Women in Adamawa and Taraba States - V, Akwa Y.; U, Umeh E.; U, Amuta E.; T, Sar T.; I, Kela S. (Darul Yasin Al Sys, 2024)
Human papillomavirus (HPV) infection is the most preval_ent sexually transmitted viral infection worldwide, especially among young, sexually active individuals. Persistent infection with high-risk HPV types significantly increases the risk of developing cervical cancer. This study investigates the socio-demographic factors associated with the risk of HPV infection among sexually active women in Adamawa and Taraba States, Nigeria. The study was conducted from June 2022 to June 2023. A structured questionnaire was administered to collect socio-demographic data. Pelvic examinations and sample collections were performed to detect HPV and cytological abnormalities. Descriptive and Chi-square analyses were conducted to explore the relationships between HPV infection and various risk factors. The result revealed that, among the participants, the analysis revealed no significant association between HPV infection and knowledge about cervical cancer or HPV, including its transmission and prevention methods. However, significant associations with HPV infection were identified for the age at first sexual intercourse, history of sexually transmitted infections (STIs), and alcohol consumption (P=0.00, 0.04, and 0.014, respectively). Age group analysis showed the highest infection rates in women aged 16-20 years. A younger age at first sexual intercourse was strongly associated with increased infection risk. Although multiple sexual partners, history of abortion, and smoking showed higher infection rates, these factors were not statistically significant. Reproductive history analysis indicated that high parity and younger age at first menstruation were significantly associated with increased risk of HPV infection. This study conclusively highlights, the importance of socio-demographic and behavioral factors in the risk of HPV infection among women in Adamawa and Taraba States. Younger age at first sexual intercourse, a history of STIs, and alcohol consumption are significant risk factors, emphasizing the need for targeted public health interventions to reduce the incidence of HPV-related diseases in these regions.